Análise dos canais de distribuição do etanol carburante brasileiro: um estudo exploratório - Lopes, Maíra Bacha (2009)
The development of flexible-fuel engines and the necessity of an alternative source of energy to the oil (Petroleum) have leaded the ethanol distribution process into a new configuration. These changes brought forth new opportunities to the Brazilian sugarcane ethanol fuel industry and new directions to the development of ethanol marketing channels in the national and international levels. In face of these macro-environmental changes, which increment the ethanol participation in the internal market, it is necessary to understand the structure of the marketing channels and how transactions between channel s members occur. In this context, the current research main goal is to characterize how the ethanol marketing channels are structured and how transactions (in the licit market) between members of this channel occur. The research was conducted as a multiple case study by collecting data from personal interviews with 14 companies representatives of the marketing channels of ethanol (sugarcane ethanol industries, marketing groups, distributors and retail stations) from the state of São Paulo, Brazil. The data analysis was conduct under the marketing channels and cost transactions economy theories. The main contributions of this research are the characterization of these marketing channels, by identifying each member s functions according to the main marketing flows for which they are responsible, how specific are the transactions and how they occur considering the governance structures between ethanol plants and fuel distributors, between fuel distributors and retail stations, and identifying the types of power involved in the process of distribution/commercialization of the ethanol fuel.